Development and evaluation of an oral liposomal vaccine for the prevention of Edwardsiellosis in Anguilla japonica caused by Edwardsiella piscicida - Young Min Woo; Keun Woo Lee; Byung-Chul Jeong; Jae Young Cha; Won-Sik Woo; Chan-Il Park; Young Jae Kim; Dong-Geun Lee; Sang-Hyeon Lee; Jun Cheul Ahn; Andre Kim (Fisheries and Aquatic Sciences)
Edwardsiellosis, caused by Edwardsiella piscicida infection in eels (Anguilla japonica), is a major problem for Korean eel farms, so there is an urgent need to develop a vaccine. For both practical and cost reasons, it is preferable to develop an oral vaccine, administration of which is significantly more efficient than injection vaccines. To avoid destruction by gastric enzymes and ensure safe delivery to the intestines, it is essential to apply a coating technology to oral vaccine antigens. To develop an oral vaccine against Edwardsiellosis, liposomes were used as an antigen coating, and the efficacy was evaluated by comparing eels’ mortality rates following oral or injection vaccination and expeirmental infection with E. piscicida. Eels that received the highest concentration oral vaccines (20 mg/fish dosage) experienced only a 6% mortality rate; those that got intraperitoneal injection vaccines had 10% mortality. In addition, the control group mortality rate (46%) was 4.18 times higher than that of the most successful oral vaccine group, confirming the efficacy of the oral vaccine. Antibody agglutination in serum extracted after oral vaccine administration confirmed the efficacy of the oral vaccine: eels that received intraperitoneal (I.P.) injection vaccines had the highest antibody agglutinationvalues (28.25 ± 0.43), but the 20 mg/fish oral vaccine group also showed high antibody agglutination (25.125 ± 1.05). These results conclusively demonstrate that the oral vaccine containing liposome-coated inactivated E. piscicida can generate an immune response sufficient to prevent Edwardsiellosis in eels.